2010
DOI: 10.1111/j.1742-6723.2009.01254.x
|View full text |Cite
|
Sign up to set email alerts
|

Verbal dyspnoea score predicts emergency department departure status in patients with shortness of breath

Abstract: Verbal dyspnoea score, alone and in combination with heart rate and arrival transport, can accurately predict admission. Once validated they might be useful in assessing, prioritizing and making rapid site of care decisions for breathless patients presenting to the ED.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 20 publications
1
14
0
Order By: Relevance
“…In our study people presenting due to breathlessness were twice as likely to be admitted as others presenting to the ED for other reasons. This increased risk is consistent with previous findings [1, 5, 7, 9]. …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In our study people presenting due to breathlessness were twice as likely to be admitted as others presenting to the ED for other reasons. This increased risk is consistent with previous findings [1, 5, 7, 9]. …”
Section: Discussionsupporting
confidence: 93%
“…Breathlessness is a feature of cardiorespiratory conditions [6] and its intensity on arrival at the ED predicts hospital admission as a post-presentation destination [7]. One clinical record review showed that a quarter of people admitted to hospital from the ED were those presenting with breathlessness [8].…”
Section: Introductionmentioning
confidence: 99%
“…Breathlessness is a frightening symptom that limits all aspects of life and is associated with poor clinical outcomes. People with breathlessness are more likely to be sent to the hospital from primary care, admitted to the hospital from the emergency department, experience a serious in‐hospital event, and have a poorer prognosis . The relationship between breathlessness and mortality is relevant for older adults; people aged 70 and older with breathlessness are less likely to live 2 and 10 years .…”
Section: Aim and Objectivesmentioning
confidence: 99%
“…14,15 Patients were asked, “On a scale from 0 to 10, how bad is your shortness of breath, with zero being no shortness of breath and 10 the worst shortness of breath you could ever imagine?” A trained research assistant asked the patients to rate dyspnea severity at admission, at 24 hours, 48 hours, and on the day of discharge. Usual or baseline dyspnea levels were assessed by asking “Using the same 0 to 10 scale, how would you rate your shortness of breath on a usual day before you became sick and came into the hospital?” At each assessment, the patients were not reminded of their prior score.…”
Section: Methodsmentioning
confidence: 99%